Influences of seawater intrusion and anthropogenic activities on shallow coastal aquifers in Sri Lanka: evidence from hydrogeochemical and stable isotope data - Jayathunga, Kaushalya; Diyabalanage, Saranga; Frank, Alexander; Chandrajith, Rohana; Barth, Johannes (Environmental Science and Pollution Research, 2020)
Water supplies in coastal aquifers throughout the world are often threatened by salinization due to seawater intrusion and anthropogenic activities. In the Kalpitiya Peninsula in Sri Lanka, agricultural and domestic water supplies entirely depend on groundwater resources extracted from unconfined Holocene sandy aquifers. To differentiate the effects of seawater intrusion and agriculture on the coastal aquifers of this 160 km2 peninsula, 43 groundwater samples were collected. These samples were analyzed for major ions, trace elements, and stable isotopes of water (δ18O and δ2H). The solute compositions were dominated by Cl−, SO42−, and HCO3−, which were mostly balanced by Ca2+, Na+, and Mg2+. Among the four main water types, Na+-Cl− and Ca2+-SO42− classifications were predominant in the investigated aquifers. Modifications of the groundwater due to evaporation during irrigation activities, but also due to seawater intrusion seem most plausible as indicated by the correlation of δ18O with δ2H (δ2H = 5.51 * δ18O-3.08, r = 0.93) deviating from the local meteoric water line. Particularly in the southern part of the peninsula, Mg2+/Ca2+ ratios and stable isotopes of water attributed salinization of groundwater to agricultural activities. However, especially in the north, seawater intrusions were also evident. Established mass balance calculations revealed that local groundwater had seawater admixtures of up to 12%. Our results indicate that integrated water management is essential and water resources should critically monitor in the Kalpitiya Peninsula in order to avoid over-exploitation and further seawater inflows.
CRIS-Team Scopus Importer:2020-05-12
Keywords: Agricultural pollution; Coastal aquifers; Irrigation return flows; Kalpitiya peninsula; Seawater intrusion